1991
DOI: 10.1016/0167-2738(91)90211-s
|View full text |Cite
|
Sign up to set email alerts
|

Electrode polarization at the Au, O2 (g) / yttria stabilized zirconia interface. Part II: electrochemical measurements and analysis

Abstract: The impedance of the Au,O,(g)/yttria stabilized zirconia interface has been measured as function of the overpotential, temperature and oxygen partial pressure. At large cathodic overpotentials (vi -0. I V) and large anodic overpotentials (7~ +O. I V) inductive effects are observed in the impedance diagram at low frequencies. Those inductive effects result from a charge transfer mechanism where a stepwise transfer of electrons towards adsorbed oxygen species occurs. A model analysis shows that the inductive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 21 publications
(22 reference statements)
3
13
0
Order By: Relevance
“…Also Re, for the Fe-YSZ has a (Po2)" dependence with m=0.25 while for the normal YSZ m varies from 0.53 (0.01 >Po_~ > 1 atm) to below 0.25 for Po2 below l0 -4 atm [ 13]. For both systems a similar exponential dependence on t/ is observed for Re, related to the anodic and cathodic charge transfer coefficients, eq.…”
Section: Electrode Propertiessupporting
confidence: 57%
See 2 more Smart Citations
“…Also Re, for the Fe-YSZ has a (Po2)" dependence with m=0.25 while for the normal YSZ m varies from 0.53 (0.01 >Po_~ > 1 atm) to below 0.25 for Po2 below l0 -4 atm [ 13]. For both systems a similar exponential dependence on t/ is observed for Re, related to the anodic and cathodic charge transfer coefficients, eq.…”
Section: Electrode Propertiessupporting
confidence: 57%
“…By implanting Fe at 50 keV (also at a dose of 8× 10 ~6 atoms cm -2) a buried layer is obtained. For these samples the conductivities measured in N 2 and in H 2 were both virtually identical of polarization (bias) using a standard three-electrode arrangement [3,13]. As platinum possesses a high activity for dissociative adsorption of oxygen, Pt electrodes can have a significant influence on the electrode reaction rate.…”
Section: Electrical Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated capacitance exhibits only a slight dependence on temperature or O 2 , in all cases ranging between 0.32 and 0.37 µF. However, general trends indicate that capacitance increases with P O 2 , which may be related to an increase in the fraction of adsorbed O 2 species at the Au/YSZ interface [11,13].…”
Section: Discussionmentioning
confidence: 89%
“…Since R S is insensitive to O 2 , average values at all O 2 concentrations are shown resulting in an E a of 93 kJ/mol, which is consistent with ionic diffusion in YSZ. An E a of 89 kJ/mole has been reported in a Au, O 2 (g)/YSZ system [11]. Hertz, et al, found differing E a for gold (88 kJ/mol) and platinum (74 kJ/mol) electrodes on thin film YSZ [12].…”
Section: Discussionmentioning
confidence: 99%